Kompetensi Guru dalam Bidang Strategi Perencanaan dan Pembelajaran Matematika - Yulinda Siregar (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2013)
One of the competences that should be must be possesses by mathematics teacher is the competence in planning the learning material, making learning material model, and designing the learning strategy for mathematics subjects. So he/she can meet the requirements to be a mathematics teacher who can do his/her duty professionally. Besides that, a teacher is required to understand and possess adequate skills in developing mathematical models of effective learning, creative and fun, as it hinted in the education unit level curriculum inspite of mathematics has high level of difficulty.